Integrasi Literasi Budaya Dan Kewarganegaraan Ke Dalam Pembelajaran Sebagai Upaya Membentuk Karakter Cinta Budaya Lokal - Shalaisa Saputri; Elsa Aulia Fadhilah; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Indonesia was born as a country that is a paradise for culture, local wisdom, ethnicity, religion and many other diverse things. There are many phenomena that show students who are not enthusiastic, are too focused on technology and modern things, consider the local culture in the area where they live to be old-fashioned, so that they do not develop a sense of love for their local culture. The aim of this research is to describe the integration of cultural literacy and citizenship into learning as an effort to shape the character of loving local culture. This research method uses the library method, this method is carried out by collecting various information through books, scientific works, theses and so on. The results of this research are that cultural and civic literacy can be integrated into learning, the form of activities can be visiting cultural tourism, playing various regional games, and even using extracurricular activities as a medium for introducing regional culture